Powaga rzeczy osądzonej w postępowaniu sądowym w sprawach z zakresu ubezpieczeń społecznych - Antonów, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In social insurance cases there is no force of res iudicata in the event of re-establishment of aright to abenefit if the person concerned refers to new evidence or disclose circumstances that had existed before the date of issuing the previous decision, should the aforementioned evidence or circumstances affect such entitlement or its amount. It is aresult of adifferent — as opposed to resumption of judicial proceedings — regulation of this institution in social insurance law, characterised by less rigorous as compared to Polish Code of Civil Procedure understanding of grounds for resumption of appeal proceedings. In particular, the “disclosed circumstances” not necessarily need to be new unknown facts and resumption of appeal proceedings is not restricted by the necessity of proving that the party could not have used them in previous proceedings. The force of res iudicata exists only when the court — hearing the appeal against the challenged decision — decides that the conditions for are-establishment of aright to abenefit have not been met, as the new decision denial of the pension authority regards the same factual and legal basis that were covered by the previous verdict.
Keywords: ubezpieczenia społeczne; postępowanie sądowe